Interleukin-10 From Marginal Zone Precursor B-Cell Subset Is Required for Costimulatory Blockade-Induced Transplantation Tolerance. Issue 9 (September 2015) - Lal, Girdhari; Nakayama, Yumi; Sethi, Apoorva; Singh, Amit K.; Burrell, Bryna E.; Kulkarni, Neeraja; Brinkman, C. Colin; Iwami, Daiki; Zhang, Tianshu; Bromberg, Jonathan S.
Abstract : Background: Blocking CD40-CD40L costimulatory signals induces transplantation tolerance. Although B-cell depletion prevents alloantibody formation, nonhumoral functions of B cells in tolerance have not been well characterized. We investigated whether specific subsets of B cell or B cell–derived interleukin (IL)-10 contribute to tolerance. Methods: Wild type C57BL/6, or B cell–specific interleukin (IL)-10 −/− (CD19-Cre +/− ::IL-10 fl/fl ) mice, received vascularized BALB/c cardiac allografts. BALB/c donor-specific splenocyte transfusion and anti-CD40L monoclonal antibody were used as tolerogen. B cells were depleted with antimouse CD20 monoclonal antibody. Various B-cell subsets were purified and characterized by flow cytometry, reverse transcription polymerase chain reaction, and adoptive transfer. Results: B-cell depletion prevented costimulatory blockade-induced allogeneic tolerance. Costimulatory blockade increased IL-10 in marginal zone precursor (MZP) B cells, but not other subsets. In particular, costimulatory blockade did not change other previously defined regulatory B-cell subsets (Breg), including CD5 + CD1d hi Breg or expression of TIM1 or TIM4 on these Breg or other Breg cell subsets. Costimulatory blockade also induced IL-21R expression in MZP B cells, and IL-21R + MZP B cells expressed even more IL-10. B-cell depletion or IL-10 deficiency in B cells prevented tolerance in a cardiac allograft model, resulting in rapid acute cardiac allograft rejection. Adoptive transfer of wild type MZP B cells but not other subsets to B cell–specific IL-10 deficient mice prevented graft rejection. Conclusions: CD40 costimulatory blockade induces MZP B cell IL-10 which is necessary for tolerance. These observations have implications for understanding tolerance induction and how B cell depletion may prevent tolerance. Abstract : Anti-CD40L mAb blockade can induce tolerance, the mechanism of which has been traditionally related to effector T cell inhibition and Treg induction. The current study shows that CD40L blockade also induces a critical subset of marginal zone precursor B cells which produce IL-10 required for tolerization. Supplemental digital content is available in the text.